Divergensi DNA Mitokondria pada Burung Pijantung Kecil (Arachnothera longirostra) dari Indonesia - Prijono, Siti Nuramaliati; Irham, Mohammad; Astuti, Dwi (Perhimpunan Biologi Indonesia, 2017)
ABSTRACTA total of 781 base pairs of mitochondrial DNA ND2 gene was analyzed to investigate their divergence in the Arachnothera longirostra (Nectariniidae) birds in Jawa and Sumatera islands of Indonesia. Blood and tissue samples were collected from 27 birds consisted of 8 samples from T.N.G. Halimun, 6 samples from T.N.G. Gede Pangrango, 6 samples from T.N. Ujung Kulon, 1 sample from Dieng (Jawa), and 6 samples from Jambi (Sumatera). Total genomic DNA was extracted from each sample and used in PCR to amplify a single fragment of mDNA ND2 gene. Their DNA sequence data were compared with those from Johor (Malaya Peninsula) and Sabah-Sarawak Borneo (GenBank). There were 61 variable sites included 34 parsimony sites and 27 sequence haplotypes. Mean genetic distance or sequence divergences within bird populasions were ranged from the lowest (0.25 %) for Ujung Kulon to the highest (0.76 %) for G. Gede Pangrango; while mean genetic distance between populations were of 1.67% to 2.82 % for Java island vs Jambi (Sumatera), and 1.06 to 2.09 % for Java vs Borneo. Phylogenetic NJ tree showed that there were two main clades, i.e. 1) birds of Jambi (Sumatra), Johor (Malay Peninsula), Sabah-Sarawak (Borneo), and Ujung Kulon (Java), and 2) birds of G. Gede Pangrango, G. Halimun, and Dieng (Java). Past geologic event may influenced genetic divergence occurred within the populations. Moreover, geographic features such as mountain may played role for population isolation as showed on the Little Spiderhunter bird from G. Halimun, G. Gede Pangrango and Dieng.Key words: mitochondrial DNA, ND2 gene, Arachnothera longirostra, genetic divergence